Microinflammation induces endothelial damage in hemodialysis patients: the role of convective transport - Ramirez, R.; Carracedo, J.; Merino, A.; Nogueras, S.; Alvarez-Lara, M.A.; Rodríguez, M.; Martin-Malo, A.; Tetta, C.; Aljama, P. (Kidney international, 2007)
Cardiovascular complications are a major cause of mortality in hemodialysis patients. On-line hemofiltration combines convective clearance for removing large solutes with diffusion to remove small solutes and is associated with a significant reduction of inflammation and improved patient survival. We compared on-line hemofiltration to high-flux hemodialysis (HF-HD) in patients in a sequential manner. At baseline, 15 stable patients on HF-HD as compared with five control subjects showed significant increases in CD14+CD16+ cells, endothelial microparticles, and endothelial progenitor cells (EPCs). After 4 months of on-line hemofiltration, the number of CD14+CD16+ cells, microparticles, and EPCs decreased. After returning to HF-HD for 4 months, all measured parameters returned to their respective baseline values. The number of CD14+CD16+ cells correlated with both endothelial microparticles and EPCs. We conclude that on-line hemofiltration attenuates endothelial dysfunction possibly by decreasing microinflammation. This effect may be directly caused by a modulatory effect of on-line hemofiltration on proinflammatory cells or by a complex interaction that encompasses a wider removal of uremic toxins.